ADULT LEARNING IN THE FIELD OF AGRICULTURE - Marioara RUSU; Violeta FLORIAN; Elisabeta ROȘU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Romania, the used agricultural area is operated by approximately 3.4 million farmers whose main feature is the fact that they have the lowest level of professional training among all European Union countries. Many of these farmers lack basic skills that are considered essential for a modern agricultural economy. The main objectives of this paper are to analyze the current conditions and the main trends in the field of adult education in the agricultural sector and to identify its strengths and weaknesses. The analysis is centered to the current European context of lifelong learning and includes: statistical benchmarks, legal and institutional framework, adult training programs, funding sources and education and training providers. The working methodology targeted three stages: identification of documentary sources and collection of data and materials for analysis; statistical processing and analysis of data and information; information synthesis. The main conclusions of this study show that Romania has a well-established legal and institutional framework for adult learning with a diverse range of funding sources for the vocational training courses. In agriculture, the main vocational training providers are the county agricultural directorates/public advisory and extension service, private firms, agricultural faculties and non-governmental organizations. However the assessment of adult vocational training quality is facing the lack of a regulatory and implementation framework has led to the discrediting, to a large extent, of this type of training.